Federal Rules of Civil Procedure (Open textbook library., 2016)
These are the Federal Rules of Civil Procedure (FRCP) as amended to December 01, 2016. The FRCP govern civil proceedings in the United States district courts and are often the foundation for the standard 1L law school course, Civil Procedure.